The Pink Pony: Burr Lafayette Mystery # 1 : murder on Mackinac Island : a Burr Lafayette mystery - Cutter, Charles (Traverse City, MI : Mission Point Press, 2020)
The world-class Port Huron Mackinac sailboat race has just finished at Mackinac Island. As soon as the boats dock, the sailors head for the legendary Pink Pony, including Jimmy Lyons and his crew. But the night takes a grisly turn, and Jimmy is found dead the next morning in the bar, strangled by a string of Christmas tree lights. Murdo Halverson, Jimmy's former partner and one of the crew, is arrested for the murder. But each of the crew had a reason to kill him, as did his wife, Jane. Burr Lafayette, recently divorced and the deposed head of the litigation department of a major Detroit law firm, is recruited to defend Murdo. A man at loose ends, Burr is a brilliant but troubled and and nearly bankrupt lawyer who prefers boats and dogs over courtrooms and clients. He's also not a criminal lawyer, and this looks like a losing case. Did Murdo kill Jimmy or was it someone else?
new book 2024 spring.
Keywords: Murder -- Investigation -- Fiction; Private investigators; Mackinac Island (Mich.) -- Fiction; Detective and mystery fiction; Fiction; Legal fiction; Detective fiction; Mystery fiction